Prospective associations between alcohol use, binge drinking and sexual activity in older adults: the English Longitudinal Study Of Ageing - Grabovac, Igor; Koyanagi, Ai; Yang, Lin; SOYSAL, PINAR; Lopez-Sanchez, Guillermo F.; McDermott, Daragh; SOYSAL, PINAR; Isik, Ahmet Turan; Veronese, Nicola; Smith, Lee (My University, 2019)
The present study aimed to investigate associations between alcohol consumption and sexual activity. Data were from 1,622 men and 2,195 women aged >= 50 years participating in the English Longitudinal Study of Ageing. Adjusted multivariable logistic regression was used to assess associations between baseline frequency of alcohol use in the last year or binge drinking in the last week and sexual activity at 8-year follow-up. Regular alcohol consumption in the last year at baseline was associated with 111% higher odds (95% CI 1.36-3.27) of any past-year sexual activity at follow-up in men and 76% higher odds (95% CI 1.26-2.46) in women. Frequent alcohol consumption was associated with 175% higher odds (95% CI 1.75-4.32) of sexual activity in men and 100% higher odds (95% CI 1.38-2.89) in women, relative to drinking alcohol never or rarely. Binge drinking was positively associated with sexual activity at follow-up, with odds of being sexually active at follow-up 52% higher (95% CI 1.07-2.15) among men who reported binge drinking at baseline and 57% higher (95% CI 1.11-2.23) among females. These findings do not outweigh the health risks associated with excessive alcohol consumption. Health practitioners should consider these findings when encouraging older adults to reduce their alcohol consumption.